Perspectives on Economic Geography in AP® Human Geography. Issue 3 (3rd May 2016) - Moore, Jon; Hunt, Allison
ABSTRACT: Economic geographers have traditionally concerned themselves with the primary and secondary sectors of the economy. As the world becomes more service-oriented, however, as much attention must be paid to the service economy and the role of technology. This article focuses on deindustrialization and the rise of the contemporary service—and technology-based economy to provide a needed conceptual framework for curriculum development and student learning. In doing so, the article presents teaching tools and concepts adapted for use in AP Human Geography classrooms.